Pengaruh Aplikasi Wattpad Terhadap Kemampuan Menulis Teks Cerita Pendek (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the effect of using the Wattpad application on the ability to write short story texts of grade XI students at SMK Negeri 1 Makassar. This research is a type of Quantitative research. The research design used in this research is One-Group Prestest-Posttest Design. The population in this study were grade XI students of SMK Negeri 1 Makassar totalling 428 students. The sampling used was simple random sampling technique. The sample in this study amounted to 50 students. The data collection technique in this study was a description test technique. The collected data were analysed with descriptive statistics and inferential statistics. The results of the students' pretest showed an average score of 50.10 in the poor category and the posttest with an average score of 81.70 in the good category. Based on the results of the Wicoxon Nonparametric test, the results of the pretest and posttest data analysis show that the sig value of 0.000 <0.05 is obtained, so Ha is accepted and H0 is rejected. This means that